DETERMINAN PEMANFATAAN POSYANDU DI PUSKESMAS TEBING SYAHBANDAR TAHUN 2023 - Tambunan, Esther Marini (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2024)
Posyandu is a form of Community-Based Health Efforts (UKBM) which is managed and organized from, by, for and with the community in implementing health development, in order to empower the community to obtain basic health services, especially to accelerate the reduction of maternal and infant mortality. The lack of utilization of posyandu as a means of monitoring the growth and development of toddlers by mothers of toddlers will result in not detecting health problems in toddlers early. This study aims to determine the determinants of the use of posyandu Tebing Syahbandar in 2022. This type of research is a type of survey with an cross-sectional approach. The population in this study were all mothers with toddlers who were in the Posyandu Tebing Syahbandar with a total sample of 96 people. Data were analyzed by bivariate and multivariate tests. Based on the results of the analysis, it was found that all variables were related to the use of posyandu including knowledge (0.03), trust (0.03), motivation (0.01), distance to health services (0.01), role of health workers (0.02 ), the role of cadres (0.01). Based on multivariate analysis, it was found that the role of cadres was the most dominant factor influencing the utilization of posyandu with Exp (B) 55,219 where cadres who had a good role 12 times would influence mothers to utilize posyandu compared to cadres who did not play a role. It is hoped that the Cadres will create a communication network that can facilitate the delivery of information to respondents who can easily convey information to all mothers who live in their work areas.